LINGKUP PENDIDIKAN ISLAM - Firmansyah, Firmansyah (STIT Ibnu Rusyd Tanah Grogot, 2022)
Education is very much needed as a process that is able to build human potential towards progress in all aspects of education according to Islam or Islamic Education. Namely, education that is understood and developed from the teachings and fundamental values contained in their basic sources, namely the AlQur'an and As-Sunnah. The purpose of writing this article is to find out about the scope of Islamic education, the method of writing this article is library research by referring to some literature and some writings in journals related to the scope of education, the results obtained from this research are that education is good if it fulfills several elements including educators, students, educational curriculum, tarbiyah and learning processes and educational institutions.